Studi Kekuatan Struktur Deck Crane Barge Terhadap Beban Knuckle Boom Crane dan Hydraulic Crane dengan Pendekatan Metode Elemen Hingga - Muhammad Aysar Santoso Santoso; Wiwin Sulistyawati (Applied Science and Technology on Naval Engineering, 2025)
This study aims to evaluate the structural strength of a crane barge deck under the loading of two types of cranes: the Knuckle Boom Crane and the Hydraulic Crane. The evaluation is conducted using the numerical Finite Element Method (FEM) with the assistance of Maxsurf Multiframe software. The main focus of the analysis is to assess the effects of crane type, boom position variation (working radius), and deck plate thickness on stress distribution and bending moment in the deck structure. The structural model used is based on an actual design of a crane barge from PT Baramulti, with dimensions adjusted to the limitations of the student version of the software. Loading scenarios were applied incrementally from 0 to 30 tons, and the results were assessed by comparing them against allowable stress limits set by the Indonesian Classification Bureau (BKI). The simulation results show that large-capacity cranes, such as the 60T Knuckle Boom Crane, generate stress levels exceeding BKI safety limits. However, after structural reinforcements were applied—such as the addition of stiffeners, increasing deck plate thickness, and changing the material to AH36—the maximum stress was reduced by approximately 26%, restoring structural safety under loads up to 20 tons. This research highlights the importance of structural design that considers crane type, actual load conditions, and material specifications to ensure the operational safety of crane barges.